Dynamic Characteristic Analysis and Clutch Engagement Test of HMCVT in the High-Power Tractor. (13th January 2021) - Chen, Yuan; Qian, Yu; Lu, Zhixiong; Zhou, Shuang; Xiao, Maohua; Bartos, Petr; Xiong, Yeping; Jin, Guanghu; Zhang, Wei
Abstract : Hydromechanical continuously variable transmission (HMCVT) is capable of bearing large torque and has wide transmission range, which is suitable for high-power tractors. Dynamic characteristics could influence the tractor life, especially in a high-power tractor. Wet clutch is the crucial component in the HMCVT, which could smooth and soft power transmission. Therefore, it is important to study the dynamic characteristics and implement the wet clutch test of HMCVT. In this paper, AMESim is used to establish virtual models of gearbox, pump-controlled hydraulic motor system, and shifting hydraulic system. Then, a simulation study of tractor operation under working condition is carried out. The internal and external meshing forces of the planetary row are analyzed. Finally, the wet clutch engagement process of HMCVT  in the high-power tractor is tested to verify the oil pressure. The simulation results show that the values of internal and external meshing force become larger as the throttle opening increases. At the moment of shifting change, the meshing forces of the planetary gear have great impact. The clutch test shows that the trend of the oil filling curve obtained from the bench test is similar to that obtained from the theoretical curve, which verifies the simulation results.